Los Mosquitos de Recipientes de Florida - Jorge R. Rey; C. Roxanne Rutledge Connelly (EDIS, 2010)
ENY860S, a 5-page illustrated fact sheet by Jorge R. Rey and Roxanne Connelly, is the Spanish language version of ENY860/IN851 Florida Container Mosquitoes. It describes the types of container mosquitoes found in Florida and recommendations for control. Includes references. Published by the UF Department of Entomology and Nematology, August 2010.